Conjunctival leiomyoma; a rare tumor of the ocular surface - Tayyab Afghani; Furqan Ahmed Khan; Hassan Mansoor (Journal of Ophthalmic & Vision Research, 2016)
Purpose: To report a case of conjuctival leiomyoma. Case Report: An 18-year-old female patient presented with a conjunctival growth in the left eye for a 2-year-period with no change in size. She merely presented for cosmetic reasons. Visual acuity was 20/20 in each eye. The lesion had prominent vessels and was not adherent to the sclera. The growth resembled a benign lesion of the conjunctiva. The tough and vascular tissue was excised and sent for histopathology. The defect was covered by an end to end conjunctival suturing. Histopathology showed the lesion to be conjunctival leiomyoma. Trichome was used to highlight the spindle shaped cells and immuno-histochemistry using anti-smooth muscle actin antibody and Vimentin was applied to confirm the diagnosis. Conclusion: This case adds to the total number of cases of conjuctival leiomyoma reported in the literature to date. An ophthalmologist needs to think beyond a common mass when encountering a conjunctival growth extending onto the cornea.